Patógenos intracelulares em carrapatos do Cerrado e Mata Atlântica: vírus e riquétsias - Pascoal, Jamile de Oliveira (2017)
In Brazil, most arthropod-transmitted viruses (arboviruses) belong to Flavivirus genus, being tick-transmitted less studied than insect-transmitted ones. Other microorganisms have great public health relevance, such as Rickettsia, the main agent of tick-borne diseases in Brazil, specially the Macular Fever (MF) group, which includes several pathogenic species that are transmitted by ticks. Within different biomes, both the Atlantic Forest and the Cerrado were severely degraded in Brazil. This thesis consisted of three chapters, aiming to identify ticks in areas of Cerrado and Atlantic Forest with surrounding human activity, looking for both Rickettsia and Flavivirus infected ticks. In the first chapter, the presence of Rickettsia was investigated in ticks from dogs and other carnivores, being eight wild carnivores species and domestic dogs in Cumari, Goiás state, Brazil. Two samples were positive for ompB gene, common in the MF group, being also positive for specific genes found in Rickettsia bellii, which does not belong to the MF group. This result shows a possible cross-infection, being tick able to maintain these two different species simultaneously. The second chapter, an 18- year-study-data from anteater ticks (Myrmecophaga tridactyla and Tamandua tetradactyla) was analyzed, accounting 169 samples evaluated for the presence of Rickettsia. Four samples were positive for ompA gene, being 100% identical to other tick sequences present in Amblyomma nodosum, indicating that Rickettsia from the MF group in A. nodosum was circulating around the city of Uberlândia and state of São Paulo. Other ticks, such as A. sculptum, could become infected by the Rickettsia presence, generating risk for domestic animals and humans. In the last chapter, ticks from six areas, being one from the Atlantic Forest and the others from the Cerrado biome, were evaluated for the presence of Flavivirus. 12 different species were accounted, in which eleven were from the Ixodidae family and one was from the Argasidae family, having the following species identified: Amblyomma sculptum, Rhipicephalus sanguineus, Rhipicephalus microplus, Dermacentor nitens, Amblyomma ovale, Amblyomma dubitatum, Amblyomma parvum, Amblyomma rotundatum, Amblyomma incisum, Amblyomma brasiliense, Amblyomma naponense and Ornithodoros sp. The presence of a Flavivirus in R. microplus ticks collected in the Uberlândia region was detected. These samples exhibited approximately 98% identity with the Mogiana Tick Virus (MGTV). All ticks that were positive for Flavivirus or Rickettsia were collected in areas with human activities, stating the importance of studies on hematophagous vectors in the epidemiology of both viral and bacterial agents in domestic and wild animals.